2018
DOI: 10.3892/mmr.2018.9490
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CCL19 benefits non‑alcoholic fatty liver disease by inhibiting TLR4/NF‑κB‑p65 signaling

Abstract: Non‑alcoholic fatty liver disease (NAFLD), which affects approximately one‑third of the general population, has become a global health problem. Thus, more effective treatments for NAFLD are urgently required. In the present study, high levels of C‑C motif ligand 19 (CCL19), signaling pathways such as Toll‑like receptor 4 (TLR4)/nuclear factor‑κB (NF‑κB), and proinflammatory factors including interleukin‑6 (IL‑6) and tumor necrosis factor‑α (TNF‑α) were detected in NAFLD patients, thereby indicating that there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
(52 reference statements)
0
14
0
1
Order By: Relevance
“…Similarly, other hepatic lipid-lowering additives also showed an anti-inflammation effect in black sea bream, such as L-carnitine and bile acid [29], choline [30] and fenofibrate [31]. Studies in mice found that berberine alleviated nonalcoholic steatohepatitis by inhibiting phosphoinositide 3-kinase (PI3K), NF-κB, and IL-8 in the cysteine X cysteine ligand 12/cysteine X cysteine receptor 4 (CXCL12/CXCR4) inflammatory signaling pathway [33], or by activating AMPK signaling and decreasing the TLR4/ NF-κB-p65 signaling pathway [34]. In addition, the antiinflammatory effect of berberine has been reported in 3T3-L1 adipocytes [35] and visceral adipose tissue [36].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other hepatic lipid-lowering additives also showed an anti-inflammation effect in black sea bream, such as L-carnitine and bile acid [29], choline [30] and fenofibrate [31]. Studies in mice found that berberine alleviated nonalcoholic steatohepatitis by inhibiting phosphoinositide 3-kinase (PI3K), NF-κB, and IL-8 in the cysteine X cysteine ligand 12/cysteine X cysteine receptor 4 (CXCL12/CXCR4) inflammatory signaling pathway [33], or by activating AMPK signaling and decreasing the TLR4/ NF-κB-p65 signaling pathway [34]. In addition, the antiinflammatory effect of berberine has been reported in 3T3-L1 adipocytes [35] and visceral adipose tissue [36].…”
Section: Discussionmentioning
confidence: 99%
“…The immunestimulating ability of berberine is attributable to its influence on enteric glial cells (EGC), bone marrow-derived dendritic glial cells (BMDCs), T cells, and gut epithelial cells (IEC) [76]. Another mechanism by which berberine modulates immune response could be by attenuating the TLR4/NF-κB-p65 signaling pathway and activating the adenosine monophosphate-(AMP-) activated protein kinase (AMPK) signaling [77].…”
Section: Discussionmentioning
confidence: 99%
“…The signals generated by TLRs are transduced through the NF-κB pathway to recruit pro-inflammatory cytokines [29], hence, the activation of the NF-κB pathway can promote the production of TNF-α, IL-1β, IL-6, and other pro-inflammatory factors, which are closely related to the development of NAFLD. Inhibiting the NF-κB signaling pathway and related inflammatory factors can significantly improve the symptoms of NAFLD in rats [30,31]. Furthermore, the progression of NAFLD to NASH requires the recruitment of activated macrophages, and CCL2 and ICAM-1 promote the activity of macrophages [32].…”
Section: Discussionmentioning
confidence: 99%